Business strategy and policy - Smith, Garry D., 1948-; Arnold, Danny R.; Bizzell, Bobby G. (Boston : Houghton Mifflin, 1991)
This book is divided into four parts: INtroduction; Environmental analysis; Strategy selection; and Taking action.
Keywords: Business; Management; Strategic planning; Strategic planning -- Case studies; Strategic planning